Peran Media Sosial dalam Memperkenalkan Program Cek Kesehatan Gratis melalui YouTube Bincang Online Inspiratif Seri 245 - Limarandani, Ni Putu (Universitas Bina Sarana Informatika, 2025)
Social media plays a crucial role in disseminating information, especially in introducing health programs. This study aims to analyze how social media, particularly YouTube, contributes to promoting the free health check program through Bincang Online Inspiratif Series 245. The research uses a qualitative method with a content analysis approach on videos published on the YouTube channel. Data collected includes view counts, comments, and viewer interactions. The findings indicate that YouTube, as a social media platform, significantly raises public awareness about the importance of free health checks. The program effectively engages a wide audience by presenting clear and accessible content. With informative and appealing communication, social media proves to be an effective tool in supporting health campaigns and educating the public. In conclusion, social media, especially YouTube, plays a key role in promoting the free health check program and educating the public about health awareness.